Kinetics of tumor size and peritumoral brain edema before, during, and after systemic therapy in recurrent WHO grade II or III meningioma - Furtner-Srajer, Julia; Schöpf, Veronika; Seystahl, Katharina; Le Rhun, Emilie; Rudà, Roberta; Roelcke, Ulrich; Koeppen, Susanne; Berghoff, Anna Sophie; Marosi, Christine; Clement, Paul; Faedi, Marina; Watts, Colin; et al. (Neuro-Oncology, 2016)
AbstractBackground. The efficacy of systemic antineoplastic therapy on recurrent World Health Organization (WHO) grades II and III meningiomas is unclear.Metho